BindingDB Entry 2196: Pyrazolyl substituted carbonic acid derivatives as modulators of the prostacyclin (PGI2) receptor useful for the treatment of disorders related thereto - BindingDB (BindingDB, 2019)
Small molecule binding data for protein Prion protein and Prostanoid IP receptor, Uniprot P04156, P43119, and Q53YK7